Small bowel adenocarcinomas in celiac disease follow the CIM-MSI pathway - Bergmann, Frank; Singh, Sandhya; Michel, Sara; Kahlert, Christoph; Schirmacher, Peter; Helmke, Burkhard Maria; Knebel Doeberitz, Magnus von; Kloor, Matthias; Bläker, Hendrik (Oncology reports, 2010)
Celiac disease (CD) is an inflammatory disorder associated with an increased risk of small bowel adenocarcinoma. Recent studies have demonstrated aberrant CpG island methylation (CIM) in chronic inflammation, aging and cancer. We hypothesized that CIM may link CD to small bowel carcinogenesis. We determined microsatellite instability (MSI), CIM, and expression of MLH1 and MGMT in 3 CD-associated small bowel carcinomas and corresponding non-neoplastic mucosa. The results were compared to those of small bowel mucosa from CD patients without carcinoma and 20 small bowel carcinomas from a non-CD origin. A high level CIM/MSI phenotype was found in all of the 3 CD-associated carcinomas and was associated with loss of MLH1 expression due to hypermethylation of the MLH1 promoter. This phenotype was noted in only 2 of the 20 investigated non-CD-associated carcinomas. Low-level CIM was already detectable in 9 of the 12 non-neoplastic mucosa samples of CD patients and in non-CD-associated carcinomas of elderly patients. In conclusion, our data reveal that the high-level CIM/MSI pathway is typical of CD-associated small bowel carcinomas and indicate that aberrant CpG island methylation links CD and carcinogenesis. The data further suggest that CD should be considered in patients with small bowel adenocarcinoma, particularly when the tumors display MSI.